(untitled) (Biological Sciences - PJSIR, 1998)
Nitrogen was used as a carrier gas with a flow velocity of 1-2 ml min’ and split ratio I: 100 and sample size 0.1 Ill. The column temperature was programmed at 70°C Ior 4 min. with 4°C min-I rise to 220°C, while dector and injector temperatures of 300°C and 250°C respectively were used, Percentage composition of individual components was calculated on the basis of peak area using a Schimadzu C-R4A chr matopac electronic integrator.